Development and characterization of microsatellite markers for Brazilian four-eyed frogs (genus Pleurodema) endemic to the Caatinga biome - Thome, M. T. C. [UNESP]; Alexandrino, J.; Lopes, S.; Haddad, C. F. B. [UNESP]; Sequeira, F. (Funpec-editora, 2014)
We used pyrosequencing to develop microsatellite markers for the Brazilian four-eyed frog Pleurodema diplolister and tested the microsatellite markers for cross-amplification in its sister Pleurodema alium, which are both endemic species of the Caatinga biome in northeastern Brazil. We used multiplex sets to amplify and genotype 30 individuals of P. diplolister from three different populations and 10 individuals of P. alium from a single population. We successfully amplified 24 loci for P. diplolister, 13 of which we were able to amplify in P. alium. All loci were polymorphic. Significant deviations from the Hardy-Weinberg equilibrium and the presence of null alleles were only consistently detected at one locus (Pleu9). These markers will enable the study of geographic genetic diversity and evolutionary processes in these two Caatinga endemics, and the inclusion of genetic data for conservation planning of the Caatinga biome.
Keywords: Pleurodema diplolister; Pleurodema alium; Caatinga; 454 shot-gun pyrosequencing